Centralized power generation with carbon capture on decommissioned offshore petroleum platforms. (15th January 2022) - Flórez-Orrego, Daniel; Freire, Ronaldo Alkmin; da Silva, Julio A.M.; Albuquerque Neto, Cyro; de Oliveira Junior, Silvio
Highlights: Power hubs have higher efficiencies than existing utility plants and 75% less emissions. Power hubs show attractive incremental net present values for carbon taxes > 40 USD/tCO2 . Carbon taxes < 80 USD/tCO2 and interest rates > 8% require carbon capture unit costs < 500 USD/kW. Capital investment halves for a delay in entry of operation of more than 2 years. Abstract: The existing cogeneration systems on offshore petroleum platforms face clashing targets intrinsic to offshore applications, namely, weight, area, cost and efficiency. Moreover, the prolonged offdesign operating conditions during their lifetime further increase the inefficiencies, leading to increased environmental impact. Thus, in this work, centralized power stations are designed for supplying the electricity required by various identical floating production, storage and offloading units (FPSOs) in the offshore oil and gas sector. This approach aims to increase the performance and alleviate the environmental burden that the conventional utility systems are responsible for by integrating carbon abatement technologies. Since these modifications bring about an increase in the initial investment cost and the financial feasibility of the system, a techno-economic assessment and optimization process is necessary in order to determine the optimal configuration of the power hubs. To this end, a combined thermodynamic, environmental and economic analysis, together with space and weight allowance quantification is performed. The use of adapted and decommissioned FPSOs for installing the power hub is a novel proposal that reduces the initial investment cost. As a result, the advanced utility systems provide higher overall power generation efficiencies (above 10 percentage points) compared to existing simple cycle gas turbine systems, even at fourfold lower emissions. The incremental economic analysis has found that, for moderate carbon taxations (> 40 USD/tCO2 ), the advanced power generation systems may economically outperform the conventional offshore power plants. Lastly, a delay in entry of operation between FPSOs of up to 4 years may reduce the investment cost by 50%, while maintains the same thermodynamic performance.